Synthesis and characterization of nickel-iron-silicon nitride nanocomposite - Marita, Yusrini; Yaacob, Iskandar Idris (Trans Tech Publications, Switzerland, 2010)
Nickel-iron-silicon nitride nanocomposite thin films were prepared by electrodeposition technique. The deposition was performed at current density of 11.5 A dm-2. Nano-size silicon nitride was mixed in the electrolyte bath as dispersed phase. The effects of silicon nitride nanoparticulates in the nickel-iron nanocomposite thin films were investigated in relation to the amount of silicon nitride in the plating bath. X-ray diffraction (XRD) analysis showed that the deposited nickel iron film has face-centered cubic structure (FCC). However, a mixture of bodycentered cubic (BCC) and face-centered cubic (FCC) phases were observed for nickel iron-silicon nitride nanocomposite films. The crystallite size of Ni-Fe nanocomposite coating decreased with increasing amount of silicon nitride in the film. From elemental mapping procedure, Si 3n4 nanopaticles were uniformly distributed in the Ni-Fe film. The presence of silicon nitride increased the hardness of the film. The microhardness of the nickel-iron nanocomposite increased from 495 HV for nickel-iron film to 846 HV for nickel-iron nanocomposite film with 2 at. % Si. The coercivity of Ni-Fe nanaocomposite films increases with decreasing crystallite size. © (2010) Trans Tech Publications.